Praktik Civic Education Penyelenggaraan Project Citizen Dalam Pendidikan Kewarganegaraan - Putri Shandefi Sinaga; Sefrina Putri; Nabilla Khairan Amaliya Chania; Rafela Putri Alfasya; ⁠Silfi Nur Aini; Alif Ramadhan (International Forum of Researchers and Lecturers, 2025)
This article discusses the practice of Civic Education through the implementation of Project Citizen in civic education in Indonesia. Taken from 15 scientific journals from 2019-2024, this study aims to explore students' understanding of active citizenship With a qualitative approach and literature review method, the application of interactive learning methods, challenges in implementation, and the positive impact produced by Project Citizen. The results of the study show that Project Citizen significantly improves students' understanding of the rights and obligations as citizens and their involvement in social issues in the community. Students involved in this project not only learn the theory, but are also able to apply it in practice, thus becoming active agents of change. However, the study also identified a number of challenges, such as lack of support from schools and limited teacher competence, that could hinder the effectiveness of project implementation. Positive impacts seen include increased student civic engagement and a sense of responsibility for the surrounding environment. Therefore, this article recommends increased support from schools, training for teachers, and collaboration between schools, parents, and communities as strategic steps to optimize the implementation of Project Citizen and improve the quality of civic education in Indonesia.